SOME BIOLOGICAL STOCK INDICATORS OF BULLET TUNA (Auxis rochei, Risso 1810) FROM BANDA SEA AND ITS ADJACENT WATERS - Khairul Amri; Afrisa Novalina; Bram Setyadji (Research Center for Fisheries, 2019)
Bullet tuna is considered as one of the important species for tuna purse seine fisheries in Indonesia, especially in archipelagic waters. However, little is known about its biological characteristics which proven to be pivotal in stock assessment. The purpose of this research was to determine some of the biological stock indicators for bullet tuna (Auxis rochei) from Banda Sea and its adjacent waters. The study was conducted from February to November 2016. The length of the bullet tuna caught were in between 18.5-32.7 cmFL (mode=24 cmFL). Growth pattern was isometric with b=3.01 and R2=0.84 Sex ratio was balanced between male and female (1:1). The spawning season allegedly from June to November. The length at 50% mature (L50) was 23.6 cmFL. A good indicator for the fisheries, where at least 75% of the mature fish caught were already spawned. The asymptotic length (L) was 33.63 cmFL, with coefficient of growth (K) around 0.73/year. Natural mortality (M) estimated at 1.87/year, fishing mortality (F) estimated at 2.20/year and total mortality (Z) was 4.07/year. The exploitation level (E) was estimated to be at maximum level (E=0.54/year), for precautionary purpose, the number of efforts should be reduced down to 8% from current effort.